Preventing Child Pedestrian Injury: A Guide for Practitioners. (November 2015) - Stevenson, Mark; Sleet, David; Ferguson, Rennie
Each year, an estimated 270, 000 pedestrians die from road traffic-related injuries, (worldwide) and children are among the most vulnerable. Child pedestrian injuries occur primarily in residential areas, often on the same street or in close proximity to the child's home, and 90% of injured child pedestrians are unaccompanied by an adult at the time of the injury. The cause of these injuries is a complex combination of factors related not only to characteristics of the child but also the built environment, the road configuration, features of the motor vehicle that might reduce injury, and driver behavior. Accordingly, effective interventions must incorporate education, technology, and improved infrastructure. The medical practitioner can not only provide the necessary education but can also be a powerful voice for changes in pedestrian infrastructure that make walking safer. This article explores the current state of childhood pedestrian injuries using examples from the United States and Australia. Pedestrian interventions and the role that primary care and lifestyle practitioners play in promoting safe pedestrian behaviors among their patients and their families are discussed.